Effect of physical conditioning with lifestyle intervention on a community-based hyperglycemic-overweight adults - Mota, João Felipe [UNESP]; Moreto, Fernando [UNESP]; Burini, Franz Homero Paganini [UNESP]; Medina, Wilson Luvizotto [UNESP]; Rimm, Eric B; Burini, Roberto Carlos [UNESP] (My University, 2011)
To evaluate the short-term (6 mo.) effectiveness of a feasible low-cost lifestyle modification program (LISC) in overweight subjects with impaired fasting glucose (IFG). We study eighty adults (>40 yrs) presenting IFG, in a six-month LISC comprising daily session of aerobic physical exercise associated with dietary counseling. A control normoglycemics group (G1, n = 40) following the LISC was matched by age, gender and BMI with the other hyperglycemic groups. The hyperglycemic subjects were divided in two groups: intervention (G2, n = 38) that effectively participated in exercise and non-exercised controls (G3, n = 42). The evaluation included anthropometry, fasting glucose and VO2max. All measurements were at baseline, three (M1) and six months (M2) after commencing LISC. At baseline, the three groups were homogeneous for age, gender, body composition and VO2max. The VO2max had increased significantly at M2 for G1 and G2. In G3 these variables remained stable throughout the experiment whereas G2 showed reduced plasma fasting glucose progressively to 7.7% at M1 and M2 14.8%, resulting in an overall reduction of IFG by 60.5%. Thus despite negligible in body fat composition, 6 months of LISC reduced efficiently the prevalence of IFG enough to save US$ millions for the national public health if applied nationwide.
Keywords: Hyperglicemia; Overweight; Lifestyle; Physical activity